THE IMPACT OF PENSIONS SAVING AND EDUCATION DEFICIT ON THE LIVING STANDARDS IN ROMANIA, IN THE POST-ACTIVITY PERIOD - SANDRA TEODORESCU (Challenges of the Knowledge Society)
The present paper starts with the study on the annual pension deficit in the EU member states, elaborated by AVIVA and DELOITTE companies in 2010. The paper analyzes the impact of pensions saving and education deficit on the living standards in Romania, in the post-activity period. It comprises the following sections: an introduction to the analysis, several definitions and the calculation method employed in the above-mentioned study, comparisons between Romania and other EU members states, focusing on the pension deficit, as well as a brief overview on the pension systems in Romania. In the end of the paper, we propose a debate on good financial planning that can make the difference between poverty and a decent standard of living at the time of retirement.